Risk Reduction in the New Financial Architecture: Realities, Fallacies, and Proposals - Martin Mayer (Levy Economics Institute of Bard College, 1999)
Five times in a decade not yet completed, financial markets have floated to the edge of a whirlpool; in October 1998 they were about to drown when Alan Greenspan threw them a piece of string that, surprisingly, turned out to be a lifeline. The causes for this financial instability lie deep–in the economic theory that urges easy and efficient substitution of one piece of paper for another, always and everywhere; in the technology-driven tight articulation of receipts and payments that Hyman Minsky warned against a generation ago; and in the growth of leverage that diminishes the creditworthiness of major institutions when an interruption in their receipts requires them to seek funds. Meanwhile, as decision-making in finance moves from banks to markets, and the creators of derivative instruments find ways to present uncertainties as risks that can be modeled, time horizons fall and spurious interrelations promote "dynamic hedging" that communicates financial disturbance anywhere to price volatility everywhere. Prevention should be sought in rules to control the creation of leverage in the repo and derivatives markets and in limits on banks' freedom to back away from borrowers' cross-border liabilities in currencies other than their own. Crisis management when prevention fails will require "standstill" agreements to encourage the continuation of something like normal economic life while the losses from merely financial failure are sorted out.
Keywords: 330